efetue as seguintes adições.
a) (2x²+9x+2)+(3x²-7x-1)=
b) (5x²+5x-8) + (-2x² + 3x-2)=
Soluções para a tarefa
Respondido por
0
Explicação passo-a-passo:
a) 2x² +9x +2 +3x² - 7x - 1=
2x² +3x² +9x - 7x +2 - 1=
5x² +2x +1
b) 5x² + 5x - 8 - 2x² + 3x - 2=
5x² - 2x² +5x + 3x - 8 - 2=
3x² + 8x - 10
Respondido por
0
Resposta:
Explicação passo a passo:
a) 2x² +9x +2 +3x² - 7x - 1=
2x² +3x² +9x - 7x +2 - 1=
5x² +2x +1
b) 5x² + 5x - 8 - 2x² + 3x - 2=
5x² - 2x² +5x + 3x - 8 - 2=
3x² + 8x - 10
Perguntas interessantes
ENEM,
6 meses atrás
História,
6 meses atrás
Pedagogia,
6 meses atrás
Física,
7 meses atrás
Matemática,
1 ano atrás